2021
DOI: 10.1186/s41256-021-00211-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of health education videos on general public’s mental health and behavior during COVID-19

Abstract: Background COVID-19 has seriously affected people's mental health and changed their behaviors. Previous studies for mental state and behavior promotion only targeted limited people or were not suitable for daily activity restrictions. Therefore, we decided to explore the effect of health education videos on people’s mental state and health-related behaviors. Methods Based on WeChat, QQ, and other social media, we conducted an online survey by snowb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…With advances in multimedia technology, modes of health education in hospitals are constantly changing, and many medical organizations in China have carried out multimedia video-based health education activities ( Yang et al, 2021 ). Animated health education videos based on multimedia broadcasting mitigate faults in traditional oral and educational manuals.…”
Section: Discussionmentioning
confidence: 99%
“…With advances in multimedia technology, modes of health education in hospitals are constantly changing, and many medical organizations in China have carried out multimedia video-based health education activities ( Yang et al, 2021 ). Animated health education videos based on multimedia broadcasting mitigate faults in traditional oral and educational manuals.…”
Section: Discussionmentioning
confidence: 99%
“…Similar barriers were recorded in a previous study conducted to assess the benefits and burdens of wearing face masks in schools during the current Corona pandemic. 22 Our intervention produced significant changes in some of these barriers such as expensive medical masks, forgetfulness, feel of embarrassment and lack of comfort ability with presence of glasses through providing the following solutions: firstly, conducting cost benefit analysis for face mask use which concluded that face mask is the cheapest and most effective way of protecting oneself and others against the coronavirus even when using the costly medical masks. Secondly, directing towards rational use of face masks through training on when, where, how to use masks appropriately and safely and what type of mask should be worn to counteract the false belief of inevitability of use of expensive medical masks which can be replaced by reusable homemade masks.…”
Section: Discussionmentioning
confidence: 99%
“…Stage 5. To test hypothesis 4 that WFC is a significant mechanism by which YS affects FH, a mediating effect analysis method ( 91 ) was applied.…”
Section: Methodsmentioning
confidence: 99%